PENGARUH PRODUK, HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN JNE AGEN PONDOK GEDE - Susilo, Herman (Jurnal Gici Jurnal Keuangan dan Bisnis, 2023)
Competition in today's business world is getting fiercer. This is also felt by business people in the field of freight forwarding services. JNE is one of the companies engaged in freight forwarding services. The research method is in the form of data collection using questionnaires, the data analysis model used is multiple linear analysis. Sample selection was carried out by purposive sampling, while the sample amounted to 97 people. Data that have met validity tests, reliability tests, and classical assumption tests are processed to produce regression equations as follows: Y= 24,699 + 0.096X1 + 0.637X2 + 0.263X3 Where the customer satisfaction variable (Y), product variable (X1), price variable (X2), and service quality variable (X3). Hypothesis testing using the t test shows that partially the product does not have a significant effect on customer satisfaction JNE Agen Pondok Gede because t calculate (0.849) < ttable (1.660) and the significance value is above 0.05, for the price variable produces tcalculate (8.519) and the service quality variable shows the results of tcalculate analysis (4.779) where ttable (1.660) and the significance value is below 0.05 then partially the two variables have a significant effect on customer satisfaction JNE agent Pondok Gede. Then through the F test, it can be seen that the three independent variables studied, namely product, price and service quality, simultaneously have a significant effect on JNE Agen Pondok Gede customer satisfaction.